Exploring Functional Differences Between Lipidated and Soluble Peptide Modulators of CMKLR1. - Heller, Daniel. (Tufts Archival Research Center, 2015)
CMKLR1 is a G protein-coupled receptor expressed by epithelial, immune, and neuronal cell types. When activated by the endogenous peptide ligand chemerin, CMKLR1 triggers a decrease in intracellular cAMP levels via coupling with the inhibitory G protein Gαi. The physiological implications of CMKLR1 activation remain unclear. We previously outlined the development of a soluble proteolysis-resistant chemerin peptide (s-sChem), and the corresponding membrane-anchored compound (l-sChem). The latter displayed anti-inflammatory effects in a mouse model of allergic airway inflammation. Understanding the mechanism by which it exerts this effect is critical for the development of therapeutics targeting CMKLR1 in humans. In this report, we describe the development of a forskolin stimulation-based assay for exploring the functional implications of chronic incubation with l-sChem on CMKLR1 signaling. Pretreatment with l-sChem decreases CMKLR1-mediated signaling in this assay, whereas s-sChem does not. Additionally, we show that l-sChem inhibits signaling of other Gαi-coupled receptors, and that this effect is mediated by CMKLR1. Finally, preliminary ELISA data suggest that the difference between s-sChem and l-sChem treatment are not due to differences in CMKLR1 expression. Further studies are needed to investigate whether the functional antagonism of CMKLR1 by l-sChem is mediated by phosphorylation of the receptor.